SERVICE MARKETING MIX AND ITS INFLUENCE ON PASSENGERS BUYING DECISION (A study at Executive Class of Bima Train for Surabaya - Malang route in PT. Kereta Api Indonesia (Persero) DAOP VIII) - Aprianto, David; Azzuhri, Misbahuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The aim of this research is to examine the service marketing mix and its influence on passengers buying decision in choosing the executive class of Bima train for Surabaya-Malang route. It focuses on investigation to reveal the effect of product, price, promotion, place, people, physical evidence and process on passengers buying decision.The samples of this research passengers of Bima train for Surabaya – Malang route. The sampling technique used was purposive sampling and the research instrument was tested using validity and reliability test. The hypotesis was tested using t test from multiple regression analysis.The result shows that product, promotion, physical evindence and process have significant effects on passengers buying decision. whilst, price, place and people have not significant effects on passengers buying decision.Keywords : Product, Price, Promotion, Place, People, Physical Evidence, Process, Passengers Buying Decision, Bima train